How human information behaviour researchers use each other's work: a basic citation analysis study - Lynne McKechnie; George R. Goodall; Darian Lajoie-Paquette; Heidi Julien (Information Research: An International Electronic Journal)
Introduction. The purpose of this study was to determine if and how human information behaviour (HIB) research is used by others. Method. Using ISI Web of Knowledge, a citation analysis was conducted on 155 English-language HIB articles published from 1993 to 2000 in six prominent LIS journals. The bibliometric core of 12 papers was identified. Content analysis was performed on papers citing the core (n=377) to determine how the papers were cited. A domain visualization was constructed of the citing relationships within the entire corpus. Analysis. Citation analysis, content analysis and social network analysi were used to analyse the data. Results. HIB literature is being cited, primarily (81.5%) by LIS authors. Fields outside of LIS citing HIB articles include engineering, psychology, education and medicine. Papers were cited generally (36.0%), for findings (28.5%) and for theory (25.3%) with few citations for method (6.0%). The domain visualization depicted a clear core of HIB scholarship surrounded by a periphery of largely uncited literature. Conclusion. HIB literature is yet to have a significant impact on other disciplines. It appears to be a second stage discipline, marked by theoretical consistency and exponential growth in publications and new researchers. More attention should be paid to writing and citation practices to allow HIB literature to become a rich guide to the act of doing HIB research.